2011
DOI: 10.1039/c1cp20552h
|View full text |Cite
|
Sign up to set email alerts
|

Growth of sputter-deposited gold nanoparticles in ionic liquids

Abstract: The growth of gold nanoparticles (NPs) synthesized by sputter deposition on an ionic liquid surface is studied in situ in the bulk phase of the ionic liquids (ILs) 1-butyl-3-methylimidazolium dicyanamide [C(1)C(4)Im][N(CN)(2)], 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)amide [C(1)C(4)Im][Tf(2)N], 1-butyl-3-methylimidazolium tetrafluoroborate [C(1)C(4)Im][BF(4)], 1-butyl-3-methylimidazolium hexafluorophosphate [C(1)C(4)Im][PF(6)] and 1-butyl-3-methylimidazolium triflate [C(1)C(4)Im][TfO]. It is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(117 citation statements)
references
References 35 publications
5
111
1
Order By: Relevance
“…This was also concluded in a study of sputter-deposited gold nanoparticles in ILs. 30 TEM analysis, conducted a few hours after the absorbance has reached a constant value, revealed that the Cu NPs are spherical with an average diameter of 3.0 ± 0.5 nm ( Figure 4A) which is consistent with the value obtained by XRD. Since only the larger NPs exhibit a SPR band, the change in the peak intensity, which is a function of the increase in the number of the Cu NPs in the system reaching this diameter, can be used as a measure of the rate at which these NPs are formed.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…This was also concluded in a study of sputter-deposited gold nanoparticles in ILs. 30 TEM analysis, conducted a few hours after the absorbance has reached a constant value, revealed that the Cu NPs are spherical with an average diameter of 3.0 ± 0.5 nm ( Figure 4A) which is consistent with the value obtained by XRD. Since only the larger NPs exhibit a SPR band, the change in the peak intensity, which is a function of the increase in the number of the Cu NPs in the system reaching this diameter, can be used as a measure of the rate at which these NPs are formed.…”
Section: Resultssupporting
confidence: 86%
“…43 It is also known that plasmon resonance bands are usually absent for very small NPs (<2.5 nm in diameter). 30 The absorption peak intensity increases as a function of time and the peak systematically shifts to higher wavelengths (610 nm, 60 minutes after the addition of NaBH 4 ). The shift of the SPR band to higher wavelengths has been attributed to aggregation of NPs.…”
Section: Resultsmentioning
confidence: 95%
“…5. After these inspiring works, the physical sputtering method flourished in the NPs synthesis [167][168][169][170][171][172].…”
Section: Noble Metalsmentioning
confidence: 99%
“…The growth of Au NPs after sputtering into 1-butyl-3-methylimidazolium dicyanamide (BMI-N(CN) 2 ), 1-butyl-3-methylimidazolium hexafluorophosphate (BMI-PF 6 ), 1-butyl-3-methylimidazolium triflate (BMI-TfO), BMI-TFSI, and BMI-BF 4 was studied by Vanecht and coworkers [22]. The sputtering experiments were performed under argon at a pressure of 0.1 mbar, an electric current of 50 mA, a sputter time of 60 s, and a target-substrate distance of 40 mm with a gold target.…”
Section: Single Materials Np Synthesismentioning
confidence: 99%
“…First, metal NP synthesis using ionic liquids will be discussed, which includes the synthesis of single material NPs and the effect of sputtering conditions [19][20][21][22][23][24][25][26][27], various alloying strategies [15,23,24,28], and techniques for transferring synthesized NPs [29][30][31]. Subsequently, we discuss NP synthesis using low-volatile polymers, including the use of thiol compounds and transfer techniques [32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%